Nonparametric Analysis of Household Labor Supply: Goodness of Fit and Power of the Unitary and the Collective Model - Cherchye, Laurens; Vermeulen, Frederic (The Review of Economics and Statistics, 2008)
We compare the empirical performance of unitary and collective labor supply models, using representative data from the Dutch DNB Household Survey. We conduct a nonparametric analysis that avoids the distortive impact of an erroneously specified functional form for the preferences and/or the intrahousehold bargaining process. Our analysis focuses on the goodness of fit of the two behavioral models. To guarantee a fair comparison, we complement this goodness-of-fit analysis with a power analysis. Our results strongly favor the collective approach to modeling the behavior of multiperson households.